From Josephus to Yosippon and beyond: text - re-interpretations - afterlives - Bay, Carson; Aviʿoz, Mikhaʾel; Henten, Jan Willem van (Journal for the study of Judaism / Supplements, 2024)
This volume marks the state-of-the-art concerning research on Flavius Josephus, Sefer Yosippon, and reception history of both. The essays contained herein draw together and build upon past research to establish a new foundation for future work on these important texts.